2011
DOI: 10.3144/expresspolymlett.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Fracture behavior of quenched poly(lactic acid)

Abstract: The effect of a quenching treatment applied on heated cast sheet extruded films of two poly(lactic acid) (PLA)\ud commercial grades, with different optical purities, was studied. The thermal and mechanical properties of the films, as well\ud as their fracture behavior, were assessed by differential scanning calorimetry (DSC), tensile tests, and the essential work of\ud fracture (EWF) approach. The heating-quenching treatment causes a de-aging effect with an increase in the free volume of\ud polymer chains evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 40 publications
5
43
0
2
Order By: Relevance
“…As PCL at room temperature is well above its glass transition temperature (T g & -60°C [32]), its amorphous phase has high compliance, which minimizes the magnitude of frozen in stresses, entropyelastic deformation. Additionally, the reported problems like the orientation, physical aging [11,33] or free-volume decrease [12] of amorphous glass phase do not interfere with the obtained results. The deformation in this state and at low deformation rates is assumed to be composed from the viscoplastic deformation of amorphous regions and the elasto-plastic deformation of crystalline spherulites.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…As PCL at room temperature is well above its glass transition temperature (T g & -60°C [32]), its amorphous phase has high compliance, which minimizes the magnitude of frozen in stresses, entropyelastic deformation. Additionally, the reported problems like the orientation, physical aging [11,33] or free-volume decrease [12] of amorphous glass phase do not interfere with the obtained results. The deformation in this state and at low deformation rates is assumed to be composed from the viscoplastic deformation of amorphous regions and the elasto-plastic deformation of crystalline spherulites.…”
mentioning
confidence: 53%
“…By these characteristics the void formation and the cavitation can be diminished or cavitation will not appear at all [8]. Additionally, below glass transition temperature (T#<%T g ) the constrained elastic deformations are favored, and problems like cold-drawing [9,10], physical aging [11] or free-volume decrease [12] of amorphous phase, interfere with the obtained results. Other viscous effects, like strain-rate dependence (see e.g.…”
mentioning
confidence: 99%
“…Figure 4 shows typical engineering stress (" N ) vs. normalized displacement (d N ) curves obtained from the EWF tests of de-aged (t a = 0 min) and 'equilibrated aged' (t a = 6 month) samples. Using a Digital Image Correlation (DIC) analysis [17,18], it was observed that for both groups of sample, the yielding process was initiated well before the maximum load was reached and from both sharpened cracks. As an example, the crack propagation onset was observed at the point indicated by the arrows as shown in Figure 4.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…In the case of PLA, which has faster physical aging than PET and PETG, the EWF analysis can only be successfully applied in the non-aged material. After 1 hour of de-aging treatment, a transient ductile-brittle situation is observed, and each tested sample shows a different behaviour [17,18]. The EWF methodology is frequently placed at the forefront of the post-yielding fracture characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al [9] grafted PLA to both ends of Pluronic F87 block copolymer (PEO-PPO-PEO) to obtain amphiphilic P(LA-b-EO-b-PO-b-EO-b-LA) block copolymers, and used these temperature-sensitive copolymers in drug release studies. High stiffness and brittleness at ambient temperatures associated with PLA can be improved by blending PLA with biodegradable plasticizer such as poly(ethylene glycol) (PEG) [12][13][14][15] or by quenching treatment applied on heated cast sheet extruded films of PLA [16]. Martin and Averous [14] plasticized PLA with several biocompatible plasticizers, such as PEG and oligomeric lactic acid, which have shown significant decrease in glass transition temperature (T g ) and rise in elongation at break.…”
mentioning
confidence: 99%